(Anti-)strangeness production in heavy-ion collisions. (January 2016) - Moreau, P.; Li, F.; Ko, C.-M.; Cassing, W.; Bratkovskaya, E. L.
Abstract: The production and dynamics of strange and antistrange hadrons in heavy-ion reactions from √sNN ≈ 3 GeV to 200 GeV is analyzed within the Parton-Hadron-String- Dynamics (PHSD) transport model. The PHSD results for strange baryon and antibaryon production are roughly consistent with the experimental data starting from upper SPS energies. Nevertheless, hadronic final state flavor-exchange reactions are important for the actual abundances, in particular at large rapidities where hadronic dynamics, parton fragmentation and string decay dominate. A striking disagreement between the PHSD results and the available data persists, however, for bombarding energies below √sNN ≈ 8 GeV where the strangeness production is significantly underestimated as in earlier HSD studies. This finding implies that the strangeness enhancement seen experimentally at FAIR/NICA energies cannot be attributed to a deconfinement phase transition or crossover but probably involves the approximate restoration of chiral symmetry in the hadronic phase.References